The role of properly structured public-private partnerships in promoting economic development. Issue 2 (14th April 2014) - Busler, Michael
Abstract : Purpose: – The purpose of this paper is to find the characteristics that determine the success of public-private partnerships (PPPs) in promoting economic development and specifically to determine the long- and short-term public involvement. Design/methodology/approach: – A grounded theory approach is utilized, involving desk research and a review of the current literature, as well as examining case studies. This reduction in data collection was based on the availability of literature and case studies which can be assimilated to develop theoretically justifiable conclusions. Findings: – In less-than-developed countries (LDC), the lack of private investment capital severely hinders economic development. In developed countries it is often high risk factors and very large capital investment that slows economic development. In both cases, an input from the public sector is needed. The findings suggest that government involvement should be time limited, so that to achieve long-term success, a public sector exit strategy should be formulated. The length of time for public sector involvement varies but is generally longer in the LDC. Research limitations/implications: – While the current literature provides some conclusions regarding the effect of PPPs on economic development, there is a gap when examining the proper structure particularly for developing countries. Originality/value: – While the current literature provides some conclusions regarding the effect of PPPs on economic development, there is a gap when examining the proper structure. This paper also provides some guidance for participants to determine the optimum length of time that public involvement is needed. Both academics and practitioners should find this to be valuable information.